Heck- and Suzuki-coupling approaches to novel hydroquinone inhibitors of calcium ATPase - Kempton, Robert J.; Kidd-Kautz, Taylor A.; Laurenceau, Soizic; Paula, Stefan (Beilstein Journal of Organic Chemistry, 2019)
In this study, we explored Heck- and Suzuki-coupling methodology to modify the template 2,5-di-tert-butylhydroquinone (BHQ, 2), an inhibitor of the enzyme sarco/endoplasmic reticulum calcium ATPase (SERCA). We found that by utilizing Suzuki coupling, we could successfully attach a six-carbon tether to BHQ that terminated in a leucine moiety to obtain target 14. Similar to related compounds based on the structure of the natural product thapsigargin, 14 displayed inhibitory potency against SERCA activity. This makes 14 a suitable candidate for the future attachment of a deactivating peptide to convey specificity for prostate cancer cells.
Keywords: calcium ATPase inhibitors; Heck- and Suzuki-coupling reactions; hydroquinones; prostate cancer; tethered amino acid